G-Force Exposure in a Contact Sport: The Use of Accelerometers to Quantify Physical Stress - McHugh, M.P; Kwiecien, S.Y; Hannon, M.P; Stewart, R.J (Journal of Sports Research, 2014)
GPS-based analyses of movement patterns are inadequate for quantifying the physical stress imposed on athletes in contact sports. Accelerometers may be useful for monitoring such athletes. The purpose of this study was to use triaxial accelerometers to record G-force exposure in Gaelic football players to examine differences in G-force exposure between games and practices and between playing positions. A small triaxial accelerometer with a flash memory chip data logger was fitted to the waistband of players’ shorts. Game and practice data were acquired at 100 Hz (scale ±16G) from 19 club level players (age 25±7 yr). Resultant G-force was: calculated for each data point from the raw accelerometer data collected in all three planes of motion and analyzed by quantifying the time spent above different G-force thresholds. Player positions were categorized as central (half backs/half forwards/midfield) and peripheral (full back/full forward) with central players typically more involved in continuous running. ANOVA with Bonferroni corrections was used to compare G-force exposure between games vs. practices, and between central vs. peripheral players (practice not position dependent). Differences between games and practices were apparent for time >3G, >4G, and >5G with more time at these thresholds in practices versus games (P=0.003), indicating higher G-force exposure in practices versus games. In games central players had greater time at >2G and >3G (P<0.001). Accelerometry analysis was effective in distinguishing player position-dependent differences in G-force exposure, and differences between games and practices. These differences indicate that the method of analysis of G-force exposure used here may be of utility for quantifying the physical stresses imposed on athletes in contact sports.